SO074VASCULAR CALCIFICATION IN PREVALENT PERITONEAL DIALYSIS PATIENTS AND ITS RELATIONSHIP WITH CLINICAL AND BONE HISTOMORFOMETRIC PARAMETERS. (6th June 2020) - Pereira, Luciano; Magalhães, Juliana; Neto, Ricardo; Oliveira, Ana; Beco, Ana; Frazao, Joao M
Abstract: Background and Aims: Vascular calcification (VC) is associated to morbidity and mortality in chronic kidney patients. However, it remains to clarify the relationship between VC and renal osteodystrophy (ROD) evaluated by bone biopsy in peritoneal dialysis (PD) patients. Method: In order to characterize the relationship between VC and ROD in prevalent PD population, we performed tetracycline-labelled bone biopsies with histomorphometric analysis according KDIGO guidelines. Hands and pelvis x-ray were performed to evaluate VC and to calculate Adragão Score. Exclusion criteria: previous kidney transplant, hemodialysis, treatment with agents interfering in bone metabolism (for example bisphosphonates). All patients were treated with biocompatible PD solutions, with calcium concentration of 1.25 mmol/L. Results: Thirty-one patients participated in the study. Mean age was 52.32±11.09 years, 16 male, 6 with diabetes mellitus (DM), 22 on manual PD, median time on PD was 12 (3-61) months. Mean calcium, phosphate and PTH were 9.2±0.5 mg/dL, 4.9±1.0 mg/dL and 486.0±230.5 pg/mL, respectively. Most frequent diagnosed ROD pattern was adynamic bone disease (44.4%) followed by hiperparathyroid bone disease (33.3%) and normal bone (14.8%). VC was detected in 29% of patients and mean Adragão score was 1.13. However, 100% of diabetics had VC on x-ray compared to 12% of non-diabetics. Clinical, analytical and histomorphometric essential data is represented in table 1: Also no significant differences were observed between the patients with or without VC in ROD patterns on bone biopsy, glucose load in PD solutions, prescribed phosphate binders namely calcium-based binders, active vitamin D or calcimimetics. In diabetic patients, bone volume tended to be lower (17.26% vs 22.54%; p=0.072) comparing to non-diabetics. Bone formation rate was similar in diabetics and non-diabetics (25.39 vs 27.71µm 3 /µm 2 /y) as mineralization lag time (18.7 vs 20.1 days). Conclusion: ROD evaluated by bone biopsy and the proportion of PD patients with VC on x-ray were similar to previous reports. However, in the present study a striking difference in VC was detected in diabetics – all diabetic patients had VC demonstrated radiographically. This finding was not explained by differences in calcium, phosphate, PTH levels or other studied factors. So DM could be a strong risk factor to VC in this population. Also, patients with VC were older, with higher sedimentation rate and lower total KT/V. It is possible that diabetic patients represent a different subgroup, particularly prone to lower bone volume and specially VC. They might benefit from higher dialysis dose and aggressive approaches to prevent or retard VC. This remains to be proved in properly designed prospective studies. In conclusion, age, sedimentation rate, total KT/V and presence of diabetes were associated to VC in prevalent PD patients. Diabetics may be a subgroup of PD patients with very high risk of VC.